Magnetic Weyl semimetal phase in a Kagomé crystal - Liu, D. F.; Liang, A. J.; Liu, E. K.; Xu, Q. N.; Li, Y. W.; Chen, Cheng; Pei, Ding; Shi, W. J.; Mo, S. K.; Dudin, Pavel; Kim, Timur; Cacho, Cephise; et al. (Science, 2019)
Weyl semimetals are crystalline solids that host emergent relativistic Weyl fermions and have characteristic surface Fermi-arcs in their electronic structure.Weyl semimetals with broken time reversal symmetry are difficult to identify unambiguously. In this work, using angle-resolved photoemission spectroscopy, we visualized the electronic structure of the ferromagnetic crystal Co3Sn2S2 and discovered its characteristic surface Fermi-arcs and linear bulk band dispersions across the Weyl points. These results establish Co3Sn2S2 as a magnetic Weyl semimetal that may serve as a platform for realizing phenomena such as chiral magnetic effects, unusually large anomalous Hall effect and quantum anomalous Hall effect.
CRIS-Team Scopus Importer:2022-04-14